AN ANALYSIS OF MAXIM OF MANNER AND MAXIM OF RELEVANCE ON FACEBOOK STATUS AND COMMENTS - Moh . Arifin (Edulitics (Education, Literature, and Linguistics) Journal, 2016)
Communication is the most often done by people, and expressingidea is one of our daily activity where their spoken or written sentence relatedto any kinds of maxims, but sometimes they have misunderstanding during thecommunication . According to H.P Grice (1913-88) the maxims are generalprinciples which are thought to underlie the efficient use of language, andwhich together identify general co-operative principle. The researcher focusesto the two maxims, the Maxim of Manner and Maxim of Relevance. Theresearcher uses descriptive qualitative design. This research is categorized asqualitative research, because the researcher presents the data by describing andinterpreting the data based on the maxims criteria. The result of the research isthat the status updaters use different utterance to show and invite thecommentators to be able to interpret the ideas go, while the commentators haveinterpretation option in interpreting the status based on the maxim criteria andthe principle of co-operation maxim. Keywords: maxims, facebook status, comment